PERKEMBANGAN JIWA AGAMA PADA ANAK - Andree Tiono Kurniawan (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
In general, a person’s religion is determined by education, experience and exercises its path in his childhood. A man who in his time never get religious education, then in later adult life , he will not feel the importance of religion in his life. As with the people who in his time had religious experiences, such as mother and father who know religious, social environment and his colleagues also run a religious life, coupled with religious education, deliberately at the home , school and community. Then people will naturally have a tendency to live within the rules of religion, accustomed to worship, fear of stepping over religious prohibitions and can feel how the joy of religious life.